THE INFLUENCE OF FINANCIAL LITERACY AND FINANCIAL INCLUSION TOWARDS MSME PERFORMANCE (A Case Study of Pananjung Market Shophouses' Owners) - Matthew Giovanni Hasiholan; Ana Noveria (Journal of Economic Development and Village Building, 2023)
This study researches the effect of financial literacy and financial inclusion simultaneously on the performance of MSMEs that have been relocated to Pananjung Market in Pangandaran Regency.  The type of research used in this research is descriptive and verification. The object studied in this study is the performance of UMKM shophouses in Pananjung Pangandaran Market. Researchers decided to use the number of MSME owners who were in the Pananjung Market Ruko as a sample of 40 people.  Financial literacy was found to have a partial impact on the MSME performance of the MSME owners of Pananjung Market Shophouses based on the partial test (t test) conducted in this study. Secondly, the MSME performance of Pananjung Pangandaran Market Shophouse MSME owners is also partially influenced by financial inclusion. The results of this study's simultaneous test (F test) indicate that financial inclusion and financial literacy have a simultaneous impact on the MSME performance of the MSME owners of Pananjung Market Shophouses.